Cerdos&Peces. A Magazine to Think about the Transgression in the Democratic Transition in Argentina (Palimpsesto, 2020)
This article is created from the hypothesis that the magazine Cerdos&Peces (1984-2004), which had a transgressive attitude with the youth sector after the Argentine dictatorship, can be considered as an exhibition device (Rogers, 2019; Benjamín, 1989). Also, there is an analysis about the ways in which the proposal of the magazine Cerdos&Peces, from its number 1 in 1984 to its number 16 in 1986, shows the declarative transgression during the democratic transition in Argentina. In this way, there will be an inquiry in the aspects chosen to be exposed and, in the ones, chosen to be overexposed in the framework of the democratic transition, focusing on what is known as the under in the sense of a transgressive platform.
Keywords: journalistic publications; democratic transition; transgression; underground